Buletin Peternakan : Kajian Produksi Aflatoksin B1 Kasar dari Isolat Kapang Aspergillus Flavus Lokal pada Media Jagung dan Jagung+Kacang Tanah - listya purnamasari, Ali Agus, Cuk Tri Noviandi (Peternakan UGM, 2016)
Aflatoxin, which known as toxigenic compound, is a secondary metabolite produced by Aspergillus flavus and A. parasiticus. Aflatoxin is found in both food and feed stuffs, such as: corn and peanut. Aflatoxin standard is needed in every research of aflatoxin contamination. But it is rather difficult to get. It is imported, high costs, and take times. The aim of the research is to assess the potential local isolate of A. flavus to producing aflatoxin that can be used to be the alternative aflatoxin standard. Local mold of A.